High-quality ceramic glaze for sanitary ceramics and preparation method of high-quality ceramic glaze
By optimizing the formula and process of ceramic glaze and reducing the amount of zirconium silicate, the problem of radioactive impurities in ceramic white glaze is solved, and a more environmentally friendly glaze preparation is achieved, cost reduction and hardness and aesthetics are maintained.
Patent Information
- Application Number
- CN202411450574.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-17
AI Technical Summary
Zirconium silicate commonly used in existing ceramic white glazes contains radioactive impurities, which leads to potential risks in human health and the environment, and its use is difficult to reduce, affecting the quality of the glaze.
Use specific formula ceramic glazes, including potassium feldspar, sodium feldspar, quartz, alumina, calcite, dolomite, firing kaolin, wollastonite, zinc oxide and boron fuses, and are processed through ball milling and magnetic separation processes. Control the amount and particle size of zirconium silicate, combine with multi-stage heating sintering to reduce radioactive impurities and maintain the hardness and beauty of the glaze surface.
It effectively reduces the radioactive indicators of glaze, complies with green environmental protection standards, reduces production costs by about 20%, and maintains the scratch resistance and service life of the glaze surface.
Smart Images

Figure CN119263638A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sanitary ceramic preparation, in particular to a high-quality ceramic glaze for sanitary ceramic and a preparation method thereof. Background Art
[0002] As people's quality of life improves, consumers have increasingly stringent requirements for sanitary ceramic glazes. They not only want the glaze to be smooth, delicate, and white, but also have higher standards for environmental friendliness. In order to achieve stable glaze quality and the required whiteness, existing ceramic white glazes usually add a certain amount of zirconium silicate. Zirconium silicate has the function of whitening and enhancing hardness, so it is widely used in ceramic glazes.
[0003] However, zircon, the main raw material of zirconium silicate, often contains radioactive elements, which leads to the presence of radioactive impurities in the prepared zirconium silicate. These impurities are difficult to remove in the ZrSiO4 structure of zirconium silicate, posing potential risks to human health and the environment. Therefore, in the actual preparation process, reducing the amount of zirconium silicate used has become a problem to be solved.
[0004] Based on this, a high-quality ceramic glaze for sanitary ceramics and a preparation method thereof are needed. Summary of the invention
[0005] To achieve the above object, the present invention provides the following solution: a high-quality ceramic glaze for sanitary ceramics, the ceramic glaze comprising by weight percentage:
[0006] Potassium feldspar: 15-23%, sodium feldspar: 4-10%, quartz: 28-34%, alumina: 1-4%, calcite: 8-14%, dolomite: 4-8%, burnt kaolin: 4-8%, wollastonite: 6-8%, zinc oxide: 2-3%, zirconium silicate: 7-10%, boron frit: 2-3%;
[0007] The boron frit has a melting temperature of 700-850°C, contains 7-10% B2O3, a Si / Al ratio of 3-3.3, and a CaO+MgO percentage of 8-10%, and does not contain alkali metal elements; the boron frit is fired in a tunnel kiln at about 1200°C, presents a phase-separated milky white color, and is introduced into the glaze formula to increase the whiteness of the glaze surface;
[0008] The particle size distribution of the zirconium silicate is: D[4,3]5-10μm, ≤2μm accounts for 55-65%, ≤10μm accounts for 75-85%, ≤20μm accounts for 85-95%, and the particle grading of the quartz is 1-3% residue on 100 mesh sieve, 80-90% residue on 250 mesh sieve, and 90-95% residue on 350 mesh sieve.
[0009] In addition, the present invention provides a method for preparing high-quality ceramic glaze for sanitary ceramics, comprising the following preparation steps:
[0010] Step 1, accurately weigh potassium feldspar, sodium feldspar, quartz, alumina, calcite, dolomite, calcined kaolin, wollastonite, zinc oxide, zirconium silicate and boron frit raw materials according to the ratio;
[0011] Step 2: Mix the above-precisely weighed raw materials with an appropriate amount of water and use a ball mill for wet grinding for 4 to 6 hours until the average particle size of the slurry is less than 10 μm;
[0012] Step 3: Sieve the ground slurry through a 200-mesh sieve to remove large particles and impurities, and then use a magnetic separation device to remove iron impurities;
[0013] Step 4: Add appropriate amount of dispersant and flow aid to the slurry after screening to adjust the drying speed and fluidity of the slurry. The pH value of the slurry after adjustment needs to be controlled at 6.5-7.5;
[0014] Step 5: Apply the glaze evenly on the surface of the sanitary ceramic body. The total thickness of the glaze layer should be controlled within 0.85-1.0 mm.
[0015] Step 6: Place the glazed body into a tunnel kiln, set the firing atmosphere to an oxidizing atmosphere, use natural gas as fuel, set the firing cycle to 15 to 20 hours, raise the temperature to 1197 to 1203°C, and maintain the temperature for 30 to 40 minutes for a sintering process.
[0016] Further preferably, the glazing equipment used in the glazing process is an automatic sprayer, and the spraying pressure is controlled at 0.3-0.5 MPa, so that the glaze is evenly distributed on the surface of the green body. At the same time, during the glazing process, the glaze should be kept at room temperature of 20°C to 25°C, so that the glaze can better adhere to the surface of the green body after spraying.
[0017] Further preferably, during the sintering process, a multi-stage heating curve is adopted, and the initial heating rate is controlled at 100°C / hour until the temperature reaches 800°C, and then the heating rate is increased to 170°C / hour until the temperature reaches 1100°C, and finally the heating rate is reduced to 50°C / hour until the maximum temperature reaches 1197~1203°C.
[0018] Further preferably, in the slurry preparation in step 4, the added dispersant is sodium polyacrylate, and the added proportion accounts for 0.1% to 0.5% of the total weight of the slurry. The dispersant is used to improve the dispersibility and stability of the slurry.
[0019] Further preferably, in the slurry preparation in step 4, the flow aid used is sodium carboxymethyl cellulose, and the addition ratio accounts for 0.5% to 1.0% of the total weight of the slurry. The flow aid is used to improve the fluidity of the slurry.
[0020] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:
[0021] 1. The white glaze formula of the present invention improves the radioactive index of ceramic products by significantly reducing the amount of zirconium silicate used. Compared with traditional formulas, the content of radioactive impurities in the formula is effectively controlled, making the product more in line with green environmental protection standards.
[0022] 2. The present invention reduces the use of zirconium silicate in the formula, but ensures that the hardness of the glaze is equivalent to that of the traditional formula by accurately adjusting the silicon-aluminum ratio and introducing quartz particles of a specific composition. Even when reducing the ingredients with potential radioactive risks, the product can still provide good scratch resistance and service life, thereby not affecting the normal use and appearance of the product.
[0023] 3. The glaze formula of the present invention reduces the amount of zirconium silicate used, thereby reducing the production cost by about 20%, thereby achieving the purpose of energy saving and consumption reduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 Schematic diagram of an embodiment
[0026] Figure 2 The radioactive detection instrument of the embodiment;
[0027] Figure 3 It is an instrument for detecting color difference and whiteness of the embodiment. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0030] Example A1
[0031] like Figure 1-3 As shown, a high-quality ceramic glaze for sanitary ceramics in this embodiment comprises, by weight percentage:
[0032] Potassium feldspar: 23%, sodium feldspar: 4%;
[0033] Quartz: 28%, with a particle size distribution of 2% residue on 100 mesh, 85% residue on 250 mesh, and 92% residue on 350 mesh;
[0034] Alumina: 1.5%, calcite: 11%, dolomite: 7%, burned kaolin: 6%, wollastonite: 8%, zinc oxide: 2.5%;
[0035] Zirconium silicate: 9%, with a particle size distribution of D[4,3]8μm, ≤2μm accounting for 60%, ≤10μm accounting for 80%, and ≤20μm accounting for 90%.
[0036] In addition, the present invention provides a method for preparing high-quality ceramic glaze for sanitary ceramics, comprising the following preparation steps:
[0037] Step 1, accurately weigh potassium feldspar, sodium feldspar, quartz, alumina, calcite, dolomite, calcined kaolin, wollastonite, zinc oxide, zirconium silicate and boron frit raw materials according to the ratio;
[0038] Step 2: Mix the above-precisely weighed raw materials with an appropriate amount of water and use a ball mill for wet grinding for 5 hours until the average particle size of the slurry is less than 10 μm;
[0039] Step 3: Sieve the ground slurry through a 200-mesh sieve to remove large particles and impurities, and then use a magnetic separation device to remove iron impurities;
[0040] Step 4: Add appropriate amounts of dispersants and flow aids to the slurry after screening to adjust the drying speed and fluidity of the slurry. The pH value of the adjusted slurry needs to be controlled at 7.0; the added dispersant is sodium polyacrylate, and the addition ratio accounts for 0.3% of the total weight of the slurry. The dispersant is used to improve the dispersibility and stability of the slurry. The flow aid used is sodium carboxymethyl cellulose, and the addition ratio accounts for 0.7% of the total weight of the slurry. The flow aid is used to improve the fluidity of the slurry;
[0041] Step 5: evenly apply the glaze to the surface of the sanitary ceramic body. The total thickness of the glaze layer should be controlled at 0.9 mm. The glazing equipment used in the glazing process is an automatic sprayer, and the spraying pressure is controlled at 0.4 MPa, so that the glaze is evenly distributed on the surface of the body. At the same time, during the glazing process, the glaze should be kept at room temperature of 22°C, so that the glaze is better attached to the surface of the body after spraying;
[0042] Step 6. Place the glazed body into a tunnel kiln, set the firing atmosphere to an oxidizing atmosphere, use natural gas as the fuel gas, set the firing cycle to 18 hours, raise the temperature to 1200°C, and maintain the temperature for 35 minutes for one sintering. During the sintering process, a multi-stage heating curve is adopted. The initial heating rate is controlled at 100°C / hour until the temperature reaches 800°C, then the heating rate is increased to 170°C / hour until the temperature reaches 1100°C, and finally the heating rate is reduced to 50°C / hour until the highest temperature reaches 1203°C.
[0043] Example A2
[0044] The ceramic glaze comprises by weight percentage:
[0045] Potassium feldspar: 23%, sodium feldspar: 4%;
[0046] Quartz: 28.5%, with a particle size distribution of 2% residue on 100 mesh, 85% residue on 250 mesh, and 93% residue on 350 mesh;
[0047] Alumina: 2%, calcite: 11%, dolomite: 7%, burned kaolin: 6%, wollastonite: 8%, zinc oxide: 2.5%;
[0048] Zirconium silicate: 8%, with a particle size distribution of D[4,3]9μm, ≤2μm accounting for 58%, ≤10μm accounting for 78%, and ≤20μm accounting for 88%.
[0049] In addition, the present invention provides a method for preparing high-quality ceramic glaze for sanitary ceramics, comprising the following preparation steps:
[0050] Step 1, accurately weigh potassium feldspar, sodium feldspar, quartz, alumina, calcite, dolomite, calcined kaolin, wollastonite, zinc oxide, zirconium silicate and boron frit raw materials according to the ratio;
[0051] Step 2: Mix the above-precisely weighed raw materials with an appropriate amount of water and use a ball mill for wet grinding for 5 hours until the average particle size of the slurry is less than 10 μm;
[0052] Step 3: Sieve the ground slurry through a 200-mesh sieve to remove large particles and impurities, and then use a magnetic separation device to remove iron impurities;
[0053] Step 4: Add appropriate amounts of dispersants and flow aids to the slurry after screening to adjust the drying speed and fluidity of the slurry. The pH value of the adjusted slurry needs to be controlled at 7.0; the added dispersant is sodium polyacrylate, and the addition ratio accounts for 0.3% of the total weight of the slurry. The dispersant is used to improve the dispersibility and stability of the slurry. The flow aid used is sodium carboxymethyl cellulose, and the addition ratio accounts for 0.8% of the total weight of the slurry. The flow aid is used to improve the fluidity of the slurry;
[0054] Step 5: evenly apply the glaze to the surface of the sanitary ceramic body. The total thickness of the glaze layer should be controlled at 0.9 mm. The glazing equipment used in the glazing process is an automatic sprayer, and the spraying pressure is controlled at 0.4 MPa, so that the glaze is evenly distributed on the surface of the body. At the same time, during the glazing process, the glaze should be kept at room temperature of 22°C, so that the glaze is better attached to the surface of the body after spraying;
[0055] Step 6. Place the glazed body into a tunnel kiln, set the firing atmosphere to an oxidizing atmosphere, use natural gas as the fuel gas, set the firing cycle to 18 hours, raise the temperature to 1200°C, and maintain the temperature for 35 minutes for one sintering. During the sintering process, a multi-stage heating curve is adopted. The initial heating rate is controlled at 100°C / hour until the temperature reaches 800°C, then the heating rate is increased to 170°C / hour until the temperature reaches 1100°C, and finally the heating rate is reduced to 50°C / hour until the highest temperature reaches 1203°C.
[0056] Example A3
[0057] The ceramic glaze comprises by weight percentage:
[0058] Potassium feldspar: 19%, sodium feldspar: 6%;
[0059] Quartz: 30%, with a particle size distribution of 2% residue on 100 mesh, 82% residue on 250 mesh, and 90% residue on 350 mesh;
[0060] Alumina: 2.5%, calcite: 12%, dolomite: 7%, burned kaolin: 7%, wollastonite: 7%, zinc oxide: 2.5%;
[0061] Zirconium silicate: 7%, with a particle size distribution of D[4,3]5μm, ≤2μm accounting for 57%, ≤10μm accounting for 76%, and ≤20μm accounting for 86%.
[0062] In addition, the present invention provides a method for preparing high-quality ceramic glaze for sanitary ceramics, comprising the following preparation steps:
[0063] Step 1, accurately weigh potassium feldspar, sodium feldspar, quartz, alumina, calcite, dolomite, calcined kaolin, wollastonite, zinc oxide, zirconium silicate and boron frit raw materials according to the ratio;
[0064] Step 2: Mix the above-precisely weighed raw materials with an appropriate amount of water and use a ball mill for wet grinding for 5 hours until the average particle size of the slurry is less than 10 μm;
[0065] Step 3: Sieve the ground slurry through a 200-mesh sieve to remove large particles and impurities, and then use a magnetic separation device to remove iron impurities;
[0066] Step 4: Add appropriate amounts of dispersants and flow aids to the slurry after screening to adjust the drying speed and fluidity of the slurry. The pH value of the adjusted slurry needs to be controlled at 6.8; the added dispersant is sodium polyacrylate, and the addition ratio accounts for 0.3% of the total weight of the slurry. The dispersant is used to improve the dispersibility and stability of the slurry. The flow aid used is sodium carboxymethyl cellulose, and the addition ratio accounts for 0.6% of the total weight of the slurry. The flow aid is used to improve the fluidity of the slurry;
[0067] Step 5: evenly apply the glaze to the surface of the sanitary ceramic body. The total thickness of the glaze layer should be controlled at 0.9 mm. The glazing equipment used in the glazing process is an automatic sprayer, and the spraying pressure is controlled at 0.4 MPa, so that the glaze is evenly distributed on the surface of the body. At the same time, during the glazing process, the glaze should be kept at room temperature of 22°C, so that the glaze is better attached to the surface of the body after spraying;
[0068] Step 6. Place the glazed body into a tunnel kiln, set the firing atmosphere to an oxidizing atmosphere, use natural gas as the fuel gas, and set the firing cycle to 18 hours. Raise the temperature to 1200°C and maintain the temperature for 35 minutes for sintering. During the sintering process, adopt a multi-stage heating curve. The initial heating rate is controlled at 50°C / hour until the temperature reaches 800°C, and then increase the heating rate to 100°C / hour until the maximum temperature reaches 1200°C.
[0069] Example A4
[0070] The ceramic glaze comprises by weight percentage:
[0071] Potassium feldspar: 18%, sodium feldspar: 6%;
[0072] Quartz: 30%, with a particle size distribution of 2% residue on 100 mesh, 85% residue on 250 mesh, and 90% residue on 350 mesh;
[0073] Alumina: 2.5%, calcite: 11%, dolomite: 7%, burnt kaolin: 7%, wollastonite: 7%, zinc oxide: 2.5%;
[0074] Zirconium silicate: 7%, with a particle size distribution of D[4,3]6μm, ≤2μm accounting for 65%, ≤10μm accounting for 85%, ≤20μm accounting for 85%;
[0075] Boron frit: 2%, with a melting temperature of 700°C, containing 7% B2O3, a Si / Al ratio of 3, 10% CaO+MgO, and no alkali metal elements.
[0076] In addition, the present invention provides a method for preparing high-quality ceramic glaze for sanitary ceramics, comprising the following preparation steps:
[0077] Step 1, accurately weigh potassium feldspar, sodium feldspar, quartz, alumina, calcite, dolomite, calcined kaolin, wollastonite, zinc oxide, zirconium silicate and boron frit raw materials according to the ratio;
[0078] Step 2: Mix the above-precisely weighed raw materials with an appropriate amount of water and use a ball mill for wet grinding for 4 hours until the average particle size of the slurry is less than 10 μm;
[0079] Step 3: Sieve the ground slurry through a 200-mesh sieve to remove large particles and impurities, and then use a magnetic separation device to remove iron impurities;
[0080] Step 4: Add appropriate amount of dispersant and flow aid to the slurry after screening to adjust the drying speed and fluidity of the slurry. The pH value of the slurry after adjustment needs to be controlled at 7.5;
[0081] The added dispersant is sodium polyacrylate, and the added proportion accounts for 0.2% of the total weight of the slurry. The dispersant is used to improve the dispersibility and stability of the slurry. The used flow aid is sodium carboxymethyl cellulose, and the added proportion accounts for 0.5% of the total weight of the slurry. The flow aid is used to improve the fluidity of the slurry;
[0082] Step 5: Apply the glaze evenly to the surface of the sanitary ceramic body. The total thickness of the glaze layer should be controlled at 0.85 mm. The glazing equipment used in the glazing process is an automatic sprayer. The spraying pressure is controlled at 0.3 MPa, so that the glaze is evenly distributed on the surface of the body. At the same time, during the glazing process, the glaze should be kept at room temperature of 20°C, so that the glaze is better attached to the surface of the body after spraying.
[0083] Step 6. Place the glazed body into a tunnel kiln, set the firing atmosphere to an oxidizing atmosphere, use natural gas as the fuel gas, set the firing cycle to 15 hours, raise the temperature to 1197°C, and maintain the temperature for 30 minutes for one sintering. During the sintering process, a multi-stage heating curve is adopted. The initial heating rate is controlled at 100°C / hour until the temperature reaches 800°C, then the heating rate is increased to 170°C / hour until the temperature reaches 1100°C, and finally the heating rate is reduced to 50°C / hour until the highest temperature reaches 1203°C.
[0084] Example A5
[0085] The ceramic glaze comprises by weight percentage:
[0086] Potassium feldspar: 18%, sodium feldspar: 6%;
[0087] Quartz: 30%, with a particle size distribution of 3% residue on 100 mesh, 90% residue on 250 mesh, and 95% residue on 350 mesh;
[0088] Alumina: 2.5%, calcite: 11%, dolomite: 6%, burned kaolin: 7%, wollastonite: 7%, zinc oxide: 2.5%;
[0089] Zirconium silicate: 7%, with a particle size distribution of D[4,3]8μm, ≤2μm accounting for 55%, ≤10μm accounting for 75%, and ≤20μm accounting for 95%;
[0090] Boron frit: 3%, with a melting temperature of 850°C, containing 10% B2O3, a Si / Al ratio of 3, 10% CaO+MgO, and no alkali metal elements.
[0091] In addition, the present invention provides a method for preparing high-quality ceramic glaze for sanitary ceramics, comprising the following preparation steps:
[0092] Step 1, accurately weigh potassium feldspar, sodium feldspar, quartz, alumina, calcite, dolomite, calcined kaolin, wollastonite, zinc oxide, zirconium silicate and boron frit raw materials according to the ratio;
[0093] Step 2: Mix the above-precisely weighed raw materials with an appropriate amount of water and use a ball mill for wet grinding for 5 hours until the average particle size of the slurry is less than 10 μm;
[0094] Step 3: Sieve the ground slurry through a 200-mesh sieve to remove large particles and impurities, and then use a magnetic separation device to remove iron impurities;
[0095] Step 4: Add appropriate amount of dispersant and flow aid to the slurry after screening to adjust the drying speed and fluidity of the slurry. The pH value of the slurry after adjustment needs to be controlled at 6.8;
[0096] The added dispersant is sodium polyacrylate, and the added ratio accounts for 0.3% of the total weight of the slurry. The dispersant is used to improve the dispersibility and stability of the slurry. The used flow aid is sodium carboxymethyl cellulose, and the added ratio accounts for 0.7% of the total weight of the slurry. The flow aid is used to improve the fluidity of the slurry;
[0097] Step 5: evenly apply the glaze to the surface of the sanitary ceramic body. The total thickness of the glaze layer should be controlled at 0.95 mm. The glazing equipment used in the glazing process is an automatic sprayer, and the spraying pressure is controlled at 0.3 MPa, so that the glaze is evenly distributed on the surface of the body. At the same time, during the glazing process, the glaze should be kept at room temperature of 24°C, so that the glaze is better attached to the surface of the body after spraying;
[0098] Step 6. Place the glazed body into a tunnel kiln, set the firing atmosphere to an oxidizing atmosphere, use natural gas as the fuel gas, set the firing cycle to 120 hours, raise the temperature to 1203°C, and maintain the temperature for 40 minutes for one sintering. During the sintering process, a multi-stage heating curve is adopted. The initial heating rate is controlled at 50°C / hour until the temperature reaches 800°C, and then the heating rate is increased to 100°C / hour until the maximum temperature reaches 1203°C.
[0099] Example A6
[0100] The ceramic glaze comprises by weight percentage:
[0101] Potassium feldspar: 18%, sodium feldspar: 6%;
[0102] Quartz: 30%, with a particle size distribution of 2% residue on 100 mesh, 88% residue on 250 mesh, and 92% residue on 350 mesh;
[0103] Alumina: 2.5%, calcite: 11%, dolomite: 6%, burned kaolin: 7%, wollastonite: 7%, zinc oxide: 2.5%;
[0104] Zirconium silicate: 7%, with a particle size distribution of D[4,3]7μm, ≤2μm accounting for 55%, ≤10μm accounting for 79%, and ≤20μm accounting for 91%;
[0105] Boron frit: 3%, with a melting temperature of 850°C, containing 10% B2O3, a Si / Al ratio of 3.3, 10% CaO+MgO, and no alkali metal elements.
[0106] The method for preparing high-quality ceramic glaze for sanitary ceramics comprises the following preparation steps:
[0107] Step 1, accurately weigh potassium feldspar, sodium feldspar, quartz, alumina, calcite, dolomite, calcined kaolin, wollastonite, zinc oxide, zirconium silicate and boron frit raw materials according to the ratio;
[0108] Step 2: Mix the above-precisely weighed raw materials with an appropriate amount of water and use a ball mill for wet grinding for 6 hours until the average particle size of the slurry is less than 10 μm;
[0109] Step 3: Sieve the ground slurry through a 200-mesh sieve to remove large particles and impurities, and then use a magnetic separation device to remove iron impurities;
[0110] Step 4: Add appropriate amount of dispersant and flow aid to the slurry after screening to adjust the drying speed and fluidity of the slurry. The pH value of the slurry after adjustment needs to be controlled at 7;
[0111] The added dispersant is sodium polyacrylate, and the added ratio accounts for 0.5% of the total weight of the slurry. The dispersant is used to improve the dispersibility and stability of the slurry. The used flow aid is sodium carboxymethyl cellulose, and the added ratio accounts for 0.9% of the total weight of the slurry. The flow aid is used to improve the fluidity of the slurry;
[0112] Step 5: Apply the glaze evenly to the surface of the sanitary ceramic body. The total thickness of the glaze layer should be controlled at 1.0 mm. The glazing equipment used in the glazing process is an automatic sprayer. The spraying pressure is controlled at 0.5 MPa, so that the glaze is evenly distributed on the surface of the body. At the same time, during the glazing process, the glaze should be kept at room temperature of 25°C, so that the glaze is better attached to the surface of the body after spraying.
[0113] Step 6. Place the glazed body into a tunnel kiln, set the firing atmosphere to an oxidizing atmosphere, use natural gas as the fuel gas, set the firing cycle to 20 hours, raise the temperature to 1197°C, and maintain the temperature for 30 minutes for one sintering. During the sintering process, a multi-stage heating curve is used. The initial heating rate is controlled at 50°C / hour until the temperature reaches 800°C, and then the heating rate is increased to 100°C / hour until the highest temperature reaches 1973°C.
[0114] Comparative Example
[0115] Table 1 below shows the recipe distribution of the original comparative example and Examples A1 to A6:
[0116]
[0117]
[0118] The whiteness, color difference and radioactivity performance of the ceramic glaze were tested for Examples A1 to A6 and the original formula, and the results are shown in Table 2;
[0119] Table 2
[0120]
[0121] Whiteness test: CM-700D spectrophotometer was used to test the glaze color difference L, a, b values; Color difference test: the original comparative example was used as the reference color plate, and the color difference values △E, △L, △a, △b between Examples A1 to A6 and them were measured;
[0122] The above whiteness and color difference are obtained by testing under the condition of standard glaze thickness of 0.65mm. Radioactivity test: BH1324F environmental gamma spectrometer is used to test the radioactivity of glaze powder after firing according to GB / T 11713-2015 "General Method for Gamma Spectrum Analysis of High Purity Germanium";
[0123] According to the test results, with the reduction of zirconium silicate dosage, the whiteness value decreases significantly, and the color difference compared with the original color sample increases; with the reduction of zirconium vanadium blue, the whiteness value has a certain upward trend, indicating that without affecting the color tone, the dosage of zirconium vanadium blue is more appropriate at 0.02%; the introduction of a certain amount of boron frit significantly improves the whiteness, because it forms multiple immiscible phases during the melting process, and these microphase conversions cause multiple refractions and scatterings of the glaze surface, thereby enhancing the glaze surface's ability to refract and scatter light, making the glaze surface present a high milky white effect;
[0124] Example B
[0125] The hardness index of this embodiment B is shown in Table 3:
[0126]
[0127] This Example B is based on Example A6, but the molar percentage of (SiO2+Al2O3) in the overall chemical composition is adjusted. The glaze hardness is tested by HM-2TE Vickers hardness tester, and the hardness value measured is the average value of five points randomly selected on the glaze surface. In addition, the melt length test is used to evaluate the flow performance of the glaze during high-temperature firing. This index directly affects the smoothness and fineness of the glaze surface. The test method is to take 5 grams of dry glaze powder to make a cylinder with a diameter of 14 mm and a height of 20 mm, and measure the length of the cylinder flowing along a 45-degree slope surface;
[0128] In Example B, as the content of (SiO2+Al2O3) increases, the crystal structure inside the glaze layer forms a -Si-O-tetrahedral network. In this structure, the Al2O3 of α-Al2O3 3+ The [AlO4] tetrahedrons are interconnected to enhance the network structure of the glaze, thereby improving the hardness of the glaze. At the same time, the quartz with a specific particle size distribution used in the present invention can increase the proportion of free quartz crystals in the microstructure of the glaze, which is also an important factor in improving the hardness of the glaze.
[0129] However, simply increasing the hardness of the glaze may shorten the high-temperature fluidity (melting length) of the glaze, thus affecting the gloss and fineness of the glaze. A melting length range of 80 to 85 mm is considered more appropriate, and the corresponding glaze hardness is 600 to 615 kgf / mm. 2 It can fully meet the production requirements.
[0130] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0131] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A high quality ceramic glaze for sanitary ceramics, characterized in that: The ceramic glaze comprises by weight percentage: Potassium feldspar: 15-23%, sodium feldspar: 4-10%, quartz: 28-34%, alumina: 1-4%, calcite: 8-14%, dolomite: 4-8%, burned kaolin: 4-8%, wollastonite: 6-8%, zinc oxide: 2-3%, zirconium silicate: 7-10%, boron frit: 2-3%.
2. A high-quality ceramic glaze for sanitary ceramics according to claim 1, characterized in that: The boron frit has a melting temperature of 700-850°C, contains 7-10% B2O3, a Si / Al ratio of 3-3.3, 8-10% CaO+MgO, and does not contain alkali metal elements. The boron frit is fired in a tunnel kiln at about 1200°C, presents a phase-separated milky white color, and is introduced into the glaze formula to increase the whiteness of the glaze.
3. A high-quality ceramic glaze for sanitary ceramics according to claim 1, characterized in that: The particle size distribution of the zirconium silicate is: D[4,3]5-10μm, ≤2μm accounts for 55-65%, ≤10μm accounts for 75-85%, ≤20μm accounts for 85-95%, and the particle grading of the quartz is 1-3% residue on 100 mesh sieve, 80-90% residue on 250 mesh sieve, and 90-95% residue on 350 mesh sieve.
4. A method for preparing high-quality ceramic glaze for sanitary ceramics according to any one of claims 1 to 3, characterized in that: The method comprises the following preparation steps: Step 1, accurately weigh potassium feldspar, sodium feldspar, quartz, alumina, calcite, dolomite, calcined kaolin, wollastonite, zinc oxide, zirconium silicate and boron frit raw materials according to the ratio; Step 2: Mix the above-precisely weighed raw materials with an appropriate amount of water and use a ball mill for wet grinding for 4 to 6 hours until the average particle size of the slurry is less than 10 μm; Step 3: Sieve the ground slurry through a 200-mesh sieve to remove large particles and impurities, and then use a magnetic separation device to remove iron impurities; Step 4: Add appropriate amount of dispersant and flow aid to the slurry after screening to adjust the drying speed and fluidity of the slurry. The pH value of the slurry after adjustment needs to be controlled at 6.5-7.5; Step 5: Apply the glaze evenly on the surface of the sanitary ceramic body. The total thickness of the glaze layer should be controlled within 0.85-1.0 mm. Step 6: Place the glazed body into a tunnel kiln, set the firing atmosphere to an oxidizing atmosphere, use natural gas as fuel, set the firing cycle to 15 to 20 hours, raise the temperature to 1197 to 1203°C, and maintain the temperature for 30 to 40 minutes for a sintering process.
5. The method for preparing high-quality ceramic glaze for sanitary ceramics according to claim 4, characterized in that: The glazing equipment used in the glazing process is an automatic sprayer, and the spraying pressure is controlled at 0.3-0.5MPa, so that the glaze is evenly distributed on the surface of the body. At the same time, during the glazing process, the glaze should be kept at room temperature of 20°C-25°C, so that the glaze can better adhere to the surface of the body after spraying.
6. The method for preparing high-quality ceramic glaze for sanitary ceramics according to claim 4, characterized in that: During the sintering process, a multi-stage heating curve is adopted. The initial heating rate is controlled at 100℃ / hour until the temperature reaches 800℃, then the heating rate is increased to 170℃ / hour until the temperature reaches 1100℃, and finally the heating rate is reduced to 50℃ / hour until the maximum temperature reaches 1197~1203℃.
7. The method for preparing high-quality ceramic glaze for sanitary ceramics according to claim 4, characterized in that: In the slurry preparation of step 4, the added dispersant is sodium polyacrylate, and the added proportion accounts for 0.1% to 0.5% of the total weight of the slurry. The dispersant is used to improve the dispersibility and stability of the slurry.
8. The method for preparing high-quality ceramic glaze for sanitary ceramics according to claim 4, characterized in that: In the slurry preparation of step 4, the flow aid used is sodium carboxymethyl cellulose, and the addition ratio accounts for 0.5% to 1.0% of the total weight of the slurry. The flow aid is used to improve the fluidity of the slurry.
Citation Information
Patent Citations
Fast-fired composite-phase microcrystal matt surface glaze slip and application thereof
CN102491788A
Sanitary ceramic sanitary appliance warm and humid glaze with soft impression and preparation process thereof
CN108455857A
White Jun-porcelain glaze
CN109369017A
Ceramic tile ground coat, ceramic tile and preparation method of ceramic tile ground coat
CN115974411A
Ceramic repair glaze composition, ceramic repair glaze and preparation method and application thereof
CN116639877A